Impact of Brown Plant Hopper (Bph) Management Training on Boro Rice Cultivation In Serajganj District (Bangladesh Journal of Agricultural Research, 2023)
A study was conducted under the project areas of Tarash Upazila at Sirajganj district. The objectives were to assess the improvement of farmers’ knowledge and perception on different factors of BPH incidence and its management to examine the economic impact on rice and to determine the profitability of Boro rice cultivation among the different groups of farms. Out of 850 samples listed, 170 representative farmers among which 16 target, 54 trained and 100 non-trained farmers were selected respectively by stratified random sampling technique. Rice plants are affected by 20-33 major insect pests. Among them, BPH is considered as most damaging one. Eighty eight, 83 and 93% target, trained and non trained farmers reported that the project needs to continue while 100% farmers of each group reported that the project is beneficial to control BPH to increase rice production. Eighty seven, 56 and 51 % farmers of the target, trained and nontrained group used double nozzle for spraying insecticides to control BPH in their field. In boro season, 2073 kg/ha and 1209 kg/ha yield loss of BRRI dhan29 were found before and after the project, respectively. The lower yield loss was due to proper management taken by the farmers who got training and acquired sufficient knowledge for controlling BPH. The study revealed that 37% higher cost and 47% higher time is required by single nozzle sprayer than double nozzle sprayer. Therefore, farmers of all categories prefer double nozzle sprayer as it is good for health and saves money and time. They also reported that use of double nozzle sprayer is more profitable than single nozzle sprayer. Benefit cost analysis indicated that the gross return, net return and BCR were found higher in case of the target farmers and these were Tk.171107/ha, Tk.73735/ha and 1.76 respectively, but the cost of production per kg was lower (Tk.10.27) than those of the other two groups due to more knowledge gathered by the target farmers on management practices for rice production. Partial budgeting analysis indicated that the double nozzle users were more benefited by Tk 7287/ha than the single nozzle users for boro rice cultivation. Thus, after the project the farmers of all categories of the project area were socio-economically benefited learning how to use double nozzle for controlling BPH.Bangladesh J. Agril. Res. 46(2): 211-226, June 2021